Answer :

(x)2 – ()2

= (x – ) (x + )


= x2 - y4


Putting x = -1 and y = -2, we have


((-1) – ) = ( (-1)2 - )


= ( - ) ( + ) = ( - )


= () () =


= =


Therefore,


L.H.S = R.H.S


Hence, verified


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Multiply the follNCERT - Mathematics Exemplar

Simplify

<
NCERT - Mathematics Exemplar

Find the followinRD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Multiply:

RD Sharma - Mathematics